An Evidence-Based Procedure for Self-Management of Medication in Hospital: Development and Validation of the SelfMED Procedure - Toke Vanwesemael; Tinne Dilles; Bart Van Rompaey; Koen Boussery (MDPI AG, 2018)
Aim: To develop and validate a procedure for self-management of medication by patients whilst in hospital. Background: Self-management of medication allows patients to self-manage their medication in a controlled and supportive hospital environment. This practice is encouraged worldwide, yet an evidence-based procedure to evaluate the ability of patients to self-manage and to monitor and support self-management are absent. Methods: The evidence-based procedure for self-management of medication (SelfMED) was developed based on previous conducted qualitative research, literature review, and the current regulation. It was validated by healthcare providers and a multidisciplinary expert meeting. Questions within the procedure that could be biased were tested for inter-rater reliability. Results: First, the SelfMED procedure was developed. It consists of a stepped assessment of patient’s competencies for self-management performed by healthcare providers and the patient. When self-management is allowed, the SelfMED monitoring tool monitors the patient’s intake of self-managed medication. Secondly, the procedure was revised for clarity, appropriateness, and face validity by five healthcare providers and a multidisciplinary expert meeting, resulting in the final version. Thirdly, three questions from the final version were tested for interrater reliability. Cohen’s Kappa showed moderate to strong levels of agreement. Conclusions: The developed SelfMED procedure provides an evidence based approach of facilitating self-management of medication. The content of the procedure was found valid to evaluate the patient’s ability to self-manage and to monitor them while self-managing.